The Epistemic Engine: Sequence Organization and Territories of Knowledge - Heritage, John (Research on language and social interaction, 2012)
This article reviews a range of conversation analytic findings concerning the role of information imbalances in the organization of conversational sequences. Considering sequences launched from knowing and unknowing epistemic stances, it considers the role of relative epistemic stance and status as warrants for the production of talk and as forces in the process of sequence production and decay.